Antenatal care service utilization in public and private sectors among women delivering at a public tertiary care centre in Northern Sri Lanka - Kumar, R.; Rahavi, R.; Narmatha, T.; Shawya, G.; Muhunthan, K.; Coonghe, P.A.D. (University of Jaffna, 2024)
Background and objective: Maternity care is provided free-of-charge through Sri Lanka’s public healthcare system. However, pregnant women who rely on the public system also access private antenatal care (ANC) on a fee-levying basis. This study describes ANC service utilization in public and private sectors among pregnant women awaiting delivery at a public tertiary hospital in Jaffna. Methods: This descriptive cross-sectional study was conducted at Teaching Hospital Jaffna (THJ). Pregnant women ≥18 years awaiting delivery after 33 weeks of gestation were recruited over a 12-week period (20/06/2022 to 09/09/2022). An interviewer-administered questionnaire was administered at the bedside and medical records reviewed to elicit sociodemographic data and details of ANC use. Data were analysed with SPSS (v21). Standard descriptive statistics and chi-square test were used in the analysis (significance level 0.05). Results: In total, 251 pregnant women participated (response rate 97.6%). The majority (80.5%, n=202) combined public ANC with private services. All participants accessed public ANC at medical officer of health clinics and 96.8% were visited at home by a public health midwife. The majority had visited public hospital clinics (76.9%) and used public laboratory services (64.9%); 35.5% had used inpatient ANC. The use of private sector services was comparatively lower; most accessed private pharmacies (60.6%), followed by channeling centres (48.2%) and laboratories (45%); only two participants reporting using private inpatient care. Median number of contacts with skilled ANC providers was 20 [IQR 17-23; public 17 (IQR 14-21); private 1 (IQR 0-5)]. Women with O/L qualifications (or higher) and those employed were 1.4 and 1.2 times more likely, respectively, to use private ANC. Both these associations were significant at the 0.05 level. Conclusions: A large proportion of pregnant women delivering at THJ use private ANC. Contacts with ANC providers in the public sector exceeded Ministry of Health and WHO guidance even in the post-COVID setting. Socioeconomic status appears to be associated with private ANC use.
Keywords: Antenatal care; Access to healthcare; Private healthcare; Maternal health; Jaffna